Heat Jet Approach for Atomic Simulations at Finite Temperature (Communications in Computational Physics, 2020)
In this paper, we propose a heat jet approach for atomic simulations at finite temperature. Thermal fluctuations are injected into an atomic subsystem from itsboundaries, without modifying the governing equations for the interior domain. Moreprecisely, we design a two way local boundary condition, and take the incoming partof a phonon representation for thermal fluctuation input. In this way, non-thermalwave propagation simulations are effectively performed at finite temperature. We furtherapply this approach to nonlinear chains with the Morse potential. Chains withmodel parameters fitted to carbon and gold are simulated at room temperature withfidelity.